1962
DOI: 10.1351/pac196204020347
|View full text |Cite
|
Sign up to set email alerts
|

Les polymères organisés

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1963
1963
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Different routes have been used to obtain liquid-crystalline polymers. One basic idea was to take a molecular group, which has a tendency to form liquid-crystalline phases (herein called an "mesogenic group"), attach it to a reactive group and perform the polymerization [7,14,151. Cases are known, where the monomers exhibit liquid-crystalline phases.…”
Section: Polymers With Liquid-crystalline Structuresmentioning
confidence: 99%
“…Different routes have been used to obtain liquid-crystalline polymers. One basic idea was to take a molecular group, which has a tendency to form liquid-crystalline phases (herein called an "mesogenic group"), attach it to a reactive group and perform the polymerization [7,14,151. Cases are known, where the monomers exhibit liquid-crystalline phases.…”
Section: Polymers With Liquid-crystalline Structuresmentioning
confidence: 99%
“…The mesomorphic phases of block polymers were first recognized and studied by Prof. Sadron and his coworkers in the course of their pioneering investigations of block polymers of styrene and ethylene oxide (44). It was suggested that the crystallization of ethylene oxide blocks is essential for the development of such phases, but eventually it was shown that mesomorphic phases are formed virtually with all block-polymer systems, e.g., in {styrene) {butadiene) system where both blocks form amorphous phases (45).…”
Section: Polymer Engineeringmentioning
confidence: 99%
“…It is well known that this process takes place at very low polymer concentrations. Below the critical micellar concentration (cmc), the insoluble block of the polymer chain collapses to form so‐called monomolecular micelles 1. Above the cmc, the soluble blocks remain in the outer part of the micelles, which is usually referred to as the corona or shell.…”
Section: Introductionmentioning
confidence: 99%